A genetic approach to understanding co-regulated MAPK genes in Arabidopsis thaliana - Ho, Bonnie Yiu (My University, 2007)
Mitogen-activated protein kinase (MAPK) signaling cascades connect cellular signal and gene transcription in cells. The pathway can regulate cell division, cell growth, and other pathways in eukaryotes. We used the Comprehensive Systems Biology Project database to find out that MPK1, 2, and 6 have a similar co-response level, as do MPK8, 19 and 20. We hypothesized that the genes in each group serve similar functions and would respond to stress similarly in Arabidopsis. We created a homozygous knockout mutant in MPK1, 2 and 6, and another one in MPK8, 19 and 20. Under normal growth conditions, the triple mutant seedlings appeared identical to wildtype seedlings. We compared the mutant and wildtype seedlings in different stress conditions (0.3 uM kinetin, 2% sucrose, 5% sorbitol, ethylene and 14°C chilling). We measured root growth of light-grown seedlings in the first three and chill treatments and hypocotyls length for sucrose-treated and ethylene-treated dark-grown seedlings. Results showed that there was no significant difference in the root or hypocotyls length growth between wildtype and mutant seedlings in all the experimental conditions. Thus, MPK1, 2, and 6 are not required in responding to stress based on the MPK1, 2, 6 triple mutant; MPK8, 19 and 20 are not required in the stress response cased on the MPK8, 19, 20 triple mutant. Future experiments have to be done to give information of their functions. This project shows a reverse genetic approach to study gene function.
16 p.
Keywords: Genetics; Biochemistry; Horticulture